Toxic by design: eliminating harmful flame retardant chemicals from our bodies, homes, & communities - Endocrine Disruptors Action Group ([s.l.], 2016)
"Toxic by Design, investigates how failures in Canada’s regulatory approach to industrial chemicals -including a new regulation on a class of toxic flame retardants called PBDEs that will come into effect on December 23, 2016 - have far-reaching effects on the health of Canadians.